Chitosan, Chitosan Derivatives and Their Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
"Chitosan, Chitosan Derivatives and Their Applications" is devoted to the latest advances in research on chitosan-based systems and focuses on highlighting scientific discoveries carried out in leading laboratories around the world. This topic is a developing field of science, but a very promising one in terms of practical applications. The manuscripts included in this book focus on all aspects of the production, modification, enzymology and application of chitin/chitosan-based systems. The reprint is divided into two parts, each of which begins with an overview article. The first half of the collected articles concerns with the application potential in agricultural and nutritional sciences. The second part covers medical and pharmaceutical applications. At the end of the presented series, several articles devoted to the synthesis and characterization of chitosan-based materials were collected. All mentioned articles (21 in total) represent a high scientific level and the latest trends in research on chitin, chitosan and their derivatives. I wish you a pleasant read.